Immune Cells as Critical Regulators of Steroidogenesis in the Testis and Beyond - Gu, Xiaowei; Li, Shu-Yun; Matsuyama, Satoko; DeFalco, Tony (Frontiers in Endocrinology, 2022)
Steroidogenesis is an essential biological process for embryonic development, reproduction, and adult health. While specific glandular cells, such as Leydig cells in the testis, are traditionally known to be the principal players in steroid hormone production, there are other cell types that contribute to the process of steroidogenesis. In particular, immune cells are often an important component of the cellular niche that is required for the production of steroid hormones. For several decades, studies have reported that testicular macrophages and Leydig cells are intimately associated and exhibit a dependency on the other cell type for their proper development; however, the mechanisms that underlie the functional relationship between macrophages and Leydig cells are unclear. Beyond the testis, in certain instances immune cells themselves, such as certain types of lymphocytes, are capable of steroid hormone production, thus highlighting the complexity and diversity that underlie steroidogenesis. In this review we will describe how immune cells are critical regulators of steroidogenesis in the testis and in extra-glandular locations, as well as discuss how this area of research offers opportunities to uncover new insights into steroid hormone production.